Analisis Proses Penerjemahan Model Wills Dalam Puisi “Illa Ummi” Karya Mahmoud Darwish - Siti Fadilah; Nanda Gema Septiani; Raden Diaz Dzikir Robby Kusuma (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the structure of the poem Illa Ummi by Mahmoud Darwish when translated using the Wills model, with a focus on the stages of the Wills translation process as applied to the poem. The research method used is a qualitative literature review. Data analysis was conducted through reading, examining, and drawing conclusions from the findings. Mahmoud Darwish was a poet born in the village of Birwa, located between Acre in the east and Galilee in the west of Palestine. The Wills model was introduced by a scholar named Wolfram Wills. The analysis process of Illa Ummi using the Wills model begins by examining the poem’s text—comprehending and breaking it down on both macro and micro levels. This includes exploring elements such as theme, imagery, language style, ‘arudh and qawafi (Arabic prosody and rhyme), emotional tone, and the poetic school or flow reflected in the poem. The next step involves aligning the source language with the target language, followed by constructing a synthesized summary from various references to produce a newly translated version.